2008
DOI: 10.1002/cncr.23191
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical modeling of endocrine response and resistance

Abstract: The authors developed a breast cancer intratumoral aromatase model system to compare the antitumor efficacy of several aromatase inhibitors (AIs) and antiestrogens (AEs). Although the AI letrozole caused sustained growth inhibition, tumors eventually began to grow, even when treatment was maintained. For the current study, the mechanisms of resistance to letrozole during the course of treatment were investigated. Estrogen receptor alpha (ER-alpha) levels decreased below control levels in letrozole-resistant tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The human epidermal GFR-2 (HER2) is significantly overexpressed, or amplified in 10% of early ERα+ breast cancers and has been associated with poor prognosis and de novo resistance to both tamoxifen and aromatase inhibitors (4)(5)(6)(7). Importantly, preclinical models have shown that the development of acquired endocrine resistance can be associated with more modest adaptive upregulation in growth factor signaling pathways (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The human epidermal GFR-2 (HER2) is significantly overexpressed, or amplified in 10% of early ERα+ breast cancers and has been associated with poor prognosis and de novo resistance to both tamoxifen and aromatase inhibitors (4)(5)(6)(7). Importantly, preclinical models have shown that the development of acquired endocrine resistance can be associated with more modest adaptive upregulation in growth factor signaling pathways (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The positive effect of the combination of anastrozole plus fulvestrant in sequence or continuously is associated with downregulation of a refractory phenotype represented by IGF-IR, AKT, MAPK, p-MAPK, mTOR, p-mTOR, and ERa expression. The combination of letrozole and fulvestrant also repressed HER2 and p-MAPK expression in the tumors treated with the combination therapy compared with tumors treated with letrozole alone (48).…”
Section: Discussionmentioning
confidence: 88%
“…Dr. Brodie has developed the ovariectomized nude mouse with estrogen-dependent MCF-7 breast cancer cells that have undergone transfection with the human aromatase gene to evaluate AI effects. 8 In this model, the combination of tamoxifen and either nonsteroidal AI, anastrozole, or letrozole, had no improved efficacy over tamoxifen alone 9 and correctly predicted the result seen in the Arimidex or Tamoxifen Alone or in Combination (ATAC) trial. 10 Most recently, this model has been used to evaluate combinations versus sequencing of endocrine and targeted therapies.…”
Section: Concurrent Versus Sequential Hormonal Therapymentioning
confidence: 84%
“…This activation may result in overexpression of human epidermal growth-factor receptor-2 neu (HER-2 neu). 8 Strategies to overcome endocrine resistance would involve the use of agents directed against the activated growth-factor pathway. Trastuzumab, which targets against HER-2 neu, may be helpful in overcoming endocrine resistance.…”
Section: Strategies For Combined Targeted Therapy To Overcome Endocrimentioning
confidence: 99%